Linguistic and Communicative Practices in the US Military’s Response to the COVID-19 Emergency - Roxanne Barbara Doerr (Lingue Culture Mediazioni, 2023)
There has been debate on the language used by the media and the government in communicating about the pandemic emergency (Kranert et al. 2020; Cardinale 2021; Kalkman 2021). One of the main criticisms lies in their extensive use of “military metaphors”, a common trend in healthcare discourse (Nie et al. 2016; Parsi 2016). In truth, the US military avoids such aggressive language in favor of a more positive professional discursive approach (Parcell and Webb 2015), with greater focus on the support and implementation of clear, structured pandemic emergency plans. As a result, the military has managed to maintain its activity and a relatively low fatality rate while becoming a model of containment in certain areas (Nevitt 2020). The study will adopt the CADS (Corpus Assisted Discourse Analysis) methodology to analyze a corpus of military press articles and Department of Defense resources. It will draw qualitative insights on productive discourse patterns of military and governmental authorities, while empirically confirming or questioning such insights. In doing so, the study aims at highlighting alternative linguistic strategies that may be productively used in civilian emergency communication.